2018
DOI: 10.7554/elife.30241
|View full text |Cite
|
Sign up to set email alerts
|

The presynaptic ribbon maintains vesicle populations at the hair cell afferent fiber synapse

Abstract: The ribbon is the structural hallmark of cochlear inner hair cell (IHC) afferent synapses, yet its role in information transfer to spiral ganglion neurons (SGNs) remains unclear. We investigated the ribbon’s contribution to IHC synapse formation and function using KO mice lacking RIBEYE. Despite loss of the entire ribbon structure, synapses retained their spatiotemporal development and KO mice had a mild hearing deficit. IHCs of KO had fewer synaptic vesicles and reduced exocytosis in response to brief depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 45 publications
7
115
0
Order By: Relevance
“…It was found previously by using electron tomography on conventionally fixed wild-type and bassoon-deficient IHC ribbon synapses that the presence of a synaptic ribbon seems to increase the number of membrane-attached tethers [21]. In RIBEYE KO mice, ribbons are absent in IHCs [25,55]. Instead, many small bassoon-containing presynaptic densities formed at IHC AZs.…”
Section: Filaments Association Defines Sv Sub-pools At Ihc Az-membranmentioning
confidence: 96%
“…It was found previously by using electron tomography on conventionally fixed wild-type and bassoon-deficient IHC ribbon synapses that the presence of a synaptic ribbon seems to increase the number of membrane-attached tethers [21]. In RIBEYE KO mice, ribbons are absent in IHCs [25,55]. Instead, many small bassoon-containing presynaptic densities formed at IHC AZs.…”
Section: Filaments Association Defines Sv Sub-pools At Ihc Az-membranmentioning
confidence: 96%
“…In contrast, genetic deletion of RIBEYE‐A in mice resulted in the complete loss of presynaptic dense bodies from retinal photoreceptors, rod bipolar cells, and cochlear hair cells . Interestingly, the functional consequences differed substantially between the latter two systems: while retinal neurotransmission was majorly impaired due to the mislocalization of presynaptic Ca 2+ channels, loss of membrane‐proximal SVs, and subsequently strongly reduced EPSC amplitudes , the cochlear phenotype of these mice was surprisingly mild.…”
Section: The Unconventional Auditory Ihc Synaptic Release Machinery –mentioning
confidence: 99%
“…Apart from unchanged synapse counts, Jean and colleagues reported extensive presynaptic developmental compensation that produced multiple ‘ribbonless’ AZs at each individual synaptic contact, thereby maintaining or even increasing the presynaptic complement of releasable SVs . Additionally, both studies consistently reported an increased size of postsynaptic densities and GluA3 receptor clusters , indicative of extensive pre‐ and postsynaptic homeostatic plasticity mechanisms aiming to compensate the loss of presynaptic release capacity. This structural reorganization in the mutants led to a minor exocytosis deficit in response to mild depolarizations that was lost upon stronger stimulation.…”
Section: The Unconventional Auditory Ihc Synaptic Release Machinery –mentioning
confidence: 99%
See 1 more Smart Citation
“…This significant functional impairment showed that RIBEYE plays a crucial role in determining the nanodomain coupling between Ca 2+ channels and synaptic vesicle exocytosis at retinal ribbon synapses. However, deletion of RIBEYE from hair cell synapses resulted in only mild hearing loss and subtle changes in the physiology of IHC synapses, suggesting a possible role of the ribbon in synaptic vesicle replenishment and/or its action as a biological buffer maintaining a constant number of vesicles at the release site (Becker et al 2018).…”
Section: Otof/glur2mentioning
confidence: 99%